Inter-region non-active site mutations in HIV-1 subtype C protease: impact on protein dynamics, stability, and drug-binding - Sherry, Dean (My University, 2021)
Human immunodeficiency virus (HIV) continues to present a significant challenge to the health of millions of individuals globally. The HIV protease enzyme is crucial for viral propagation and, as such, it is a major drug target in anti-retroviral therapy. However, the high replicative rate of the virus and the mutation-prone nature of reverse transcription leads to sequence polymorphisms which compound the difficulty of effective treatment. Indeed, the development of inhibitor resistance remains a significant stumbling block for successful anti-HIV therapy. Drug resistance begins with active site mutations which directly decrease drug binding through altering the geometry of the active site. Non-active site mutations have long been thought to play a compensatory role for the potentially deleterious effects of active site mutations. However, their role in drug resistance cannot be understated as multi-drug resistant variants must accumulate constellations of non-active site mutations in order to establish high levels of resistance. The role that these mutations play in resistance has not been fully explained, however, it has been hypothesised that their presence alters the hydrophobic sliding mechanism which is thought to be responsible for modulating the conformation of the flaps. In this research, a South African subtype C protease variant (named HP3 PR) was investigated. This variant contains the following polymorphisms which have been correlated with decreased drug susceptibility; namely, I13V, I62V, and V77I.A novel crystal structure of the HP3 PR was solved and, through structural, functional, and in silico analyses a mechanism of resistance was elucidated. The resistance mechanism appears to work in two parts: eliciting changes in the behaviour of the apo as well as the ligand-bound states of the protein. Thermodynamic and differential scanning calorimetric analyses revealed that the HP3 protease binds to certain clinical inhibitors with decreased binding affinity and that the inhibitor bound protease complex exhibits decreased thermal stability. In silico analyses revealed an increased preference for the closed flap conformation when in the apo state alongside increased structural rigidity of distinct regions of the protease. Thus, the apo HP3 protease requires an increased energetic penalty for the conformational changes required for drug binding, which contributes to decreased favourability of drug binding. Secondly, the ligand-bound protease exhibited wider flap conformations (semi-open) with an increased degree of flap flexibility and ligand mobility within the active site. The inhibitor-bound protease complexes therefore exhibit diminished stability though minimising intermolecular interactions and resisting closing of the flaps in the presence of inhibitors. Collectively, these data elucidate the biophysical basis for the selection of non-active site mutations in the protease and how these mutations contribute to inhibitor resistance. By shifting the drug resistance paradigm to incorporate the dynamic nature of the enzyme and enzyme-complexes a better understanding of resistance mechanisms is made salient. [452]
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, 2021